1978
DOI: 10.1002/cne.901820204
|View full text |Cite
|
Sign up to set email alerts
|

GABA‐ergic pathways in the goldfish retina

Abstract: A high-affinity uptake mechanism for [3H]-gamma-aminobutyric acid (GABA) has been localized to type H1 cone horizontal cells and type Ab pyriform amacrine cells in the retina of the goldfish by light and electron microscopy autoradiography. By stimulating isolated retinas with colored lights during incubation we have been able to use [3H]-GABA uptake as a probe of light-evoked changes in membrane potential. All colors of lights increase and darkness decreases [3H]-GABA uptake by H1 cone horizontal cells. Our m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
161
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 338 publications
(173 citation statements)
references
References 50 publications
12
161
0
Order By: Relevance
“…As cones are minute cells, the electrode did not stay intracellularly located long enough to observe slowly appearing effects from lower concentrations of GABA. If one also considers the high-affinity uptake mechanisms of GABA into horizontal cells (MARC et al, 1978), it is reasonable to suppose that the concentration of externally applied GABA is gradually reduced during diffusion en route to the GABA-sensitive site in cones, and that the final concentration does not differ greatly from the effective concentration at the invertebrate neuromuscular junction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As cones are minute cells, the electrode did not stay intracellularly located long enough to observe slowly appearing effects from lower concentrations of GABA. If one also considers the high-affinity uptake mechanisms of GABA into horizontal cells (MARC et al, 1978), it is reasonable to suppose that the concentration of externally applied GABA is gradually reduced during diffusion en route to the GABA-sensitive site in cones, and that the final concentration does not differ greatly from the effective concentration at the invertebrate neuromuscular junction.…”
Section: Discussionmentioning
confidence: 99%
“…The early studies were reviewed by GRAHAM (1974) andVOADEN (1976). Our interest has been quickened by a series of reports published by Lam and others, in which they suggested that, in the fish retina, GABA is a neurotransmitter mediating the feedback synaptic pathways from horizontal cells to cones (LAM and STEINMAN, 1971;LAM, 1975LAM, , 1976MARC et al, 1978;LAM et al, 1979).…”
mentioning
confidence: 99%
“…The delay and the polarity reversal seemed to indicate a chemical junction. In the lower vertebrates which were the main object of study in the 1970s and 1980s, horizontal cells are GABAergic (Marc et al, 1978) and much energy was expended in trying to prove that feedback to cones operated through a GABA-dependent mechanism. In spite of many claims and counterclaims, however (reviewed in Burkhardt, 1993;Kamermans and Spekreijse, 1999), a GABAergic basis for feedback could not be established firmly.…”
Section: Feedback From Horizontal Cells To Conesmentioning
confidence: 99%
“…Retinas were fixed in 2.5% glutaraldehyde/1% paraformaldehyde, dehydrated, embedded in epoxy resin, sectioned (250 nm), and processed for light microscope autoradiography as described by Marc and Liu (1985). In detail, 250-nm sections were placed at 25 mm from the end of a glass slide, dipped in 1:1 aqueous Kodak NTB-3 at 40°C and dried at an angle of 70°C, were exposed for 15 days, developed in 1:1 aqueous Kodak Dektol at 16°C, fixed, washed, dried, and stained with toluidine blue as specified in Marc et al (1978). This protocol allows for precise, quantitative comparisons of labeling across specimens.…”
Section: Glutamate Uptake: [ 3 H]d-asp Autoradiographymentioning
confidence: 99%